PEMAHAMAN TRITUNGGAL DALAM SEJARAH PENYATAAN ALLAH: ANALISIS PERICHORESIS DALAM PEMIKIRAN D. GLENN BUTNER JR. - Saut Sihombing; Refamati Gulo (Jurnal Teologi RAI, 2024)
The doctrine of the Trinity is one of the doctrines that most often becomes a polemic both among Christians and outside Christianity. In general, the concept of the Trinity is considered as something irrational. The aim of this research is to provide an understanding of the doctrine of the Trinity based on God's Word so that it can be a teaching for Christians in particular and readers in general. In addition, it provides an understanding of the history of the Trinity from the early church and also the progression of the Trinity throughout scripture. The God we can know is limited to what is stated in the Bible and the God who reveals himself in the Bible is the Triune God, this is what Christians must understand. The method used is qualitative with a descriptive analysis approach. The results of this research indicate that D. Glenn Butner Jr's work in Perichoresis is part of a broader exploration of Trinitarian theology with the aim of providing a comprehensive understanding of Christian doctrine about God.